Construction and characterization of phage-display and bacteriophage-mediated vaccines against very virulent infectious bursal disease and genotype VII newcastle disease - Al-Tayyar, Omar Bassim Ahmed (2018)
Newcastle disease (ND) is regarded as one of the most significant viral diseases in the poultry industry and perhaps it presents the larger drainage to the world economy when it is compared to various other animal viruses. The main antigens are the F and HN genes. Infectious bursal disease (IBD) remains a constant intimidation to the world poultry industry. In addition to the high mortalities of very virulent IBD, the most important is the immuno-suppression that it causes. VP2 is the major antigen. Although, attenuated live vaccines and inactivated vaccines have been used in the field since the last century to control these diseases, the need for more safe and more efficacious vaccines is still required. This study was undertaken to develop phage-display and bacteriophage-mediated vaccines against both Newcastle disease and infectious bursal disease based on F and VP2 protein sequences. The study hypothesis is that Phage-display vaccines and bacteriophage-mediated vaccines are able to induce protective immune response in vaccinated chickens. Bacteriophage (phage)-display (PD) and bacteriophage-mediated (BM) immunization are novel vaccines delivery technology. In PD vaccine the inserted gene is displayed as a protein on the surface of the phage. While in BM vaccine the phage act as gene transfer vector. They have many advantages over the conventional vaccines. The first approach was the construction of the vaccines. PD vaccines were constructed using VP2 of vvIBD (UPM0081) as (pha.Dis-VP2) and F for ND genotype VII (IBS002) as (pha.Dis-F) consequently. BM vaccines were constructed using VP2 of vvIBD (UPM0081) as (pha.Med-VP2) and F for ND genotype VII (IBS002) as (pha.Med-F) subsequently. After sequencing and conformation of the vaccines, their functionality was assessed through Western blotting. The results of the Western blot indicate that the antigens in the PD and BM vaccines were successfully expressed in the hd11 cell line. In the first chicken trial, the pha.Dis-VP2 vaccine was administered via three different delivery routes (orally, subcutaneously and subcutaneously-in oil) into specific pathogen-free (SPF) chickens groups. The vaccination program consisted of two vaccinations with three weeks apart to stimulate the immune response. After each vaccination blood withdrawal from the wing vein was performed to detect the immune respond translated as antibodies titer. The same procedure was accomplished for the pha.Dis-F vaccine were it was administered orally, subcutaneously and subcutaneously-in oil. Three weeks post booster vaccination the challenge was carried out using vvIBDV for the pha.Dis-VP2 vaccinated groups, and vvNDV for the pha.Dis-F groups. The results of this trial revealed, for the first time, that pha.Dis-VP2 vaccine administered orally provides the best protection (93.34%) for the vaccinated chickens against the challenge with the vvIDBV, while the protection of the subcutaneous and subcutaneous-in oil adjuvant vaccination was (80%) and (66.67%) respectively. The detected antibodies titer was significantly higher (p< 0.01) in the oral vaccinated group, using a VP2-based ELISA kit, followed by the subcutaneous and subcutaneous-in oil adjuvant vaccinated groups consequently. The results of the bursal/body weight ratio for the vaccinated chickens indicates that the vaccine in the oral group have no detrimental effects on the bursae and that the vaccine successfully protected the bursae from the challenge impact. The histopathological assessment revealed similar pattern as a bursal lesion scores. Concerning ND vaccination, unfortunately the pha.Dis-F vaccination did not protect any of the vaccinated chickens groups after the challenge with the highly virulent strain of NDV genotype VII (IBS002), but delayed the mortalities of the chickens. In the second chicken trial, the pha.Dis-VP2 vaccine was administered via the oral route into SPF chicken group. The vaccination program included two vaccinations with three weeks interval to boost the immune response. Blood withdrawal was carried out from the wing vein to detect the immune respond expressed as antibodies titer. The same procedure was accomplished for the pha.Med-F vaccine. Three weeks after the second vaccination the challenge was carried out using vvIBDV for the pha.Med-VP2 vaccinated group, and vvNDV for the pha.Med-F group. The results of this trial revealed, for the first time, that pha.Med-VP2 vaccine administered orally provided a protection of (92.31%) for the vaccinated chickens against the challenge with the vvIDBV. The detected antibodies titer was significantly higher (p< 0.01) in the vaccinated group, using a VP2-based ELISA kit. The results of the bursal/body weight ratio for the vaccinated chickens indicates that the vaccine have no detrimental effects on the bursae and that the vaccine successfully protected the bursae from the challenge impact. The histopathological assessment revealed similar pattern as a bursa lesion scores. Concerning ND vaccination, unfortunately the pha.Med-F vaccination did not protect the vaccinated chickens group after the challenge with the highly virulent strain of NDV genotype VII (IBS002), but delayed the mortalities. In conclusion, the constructed VP2-recombinant vaccines were immunogenic in SPF chickens. Phage-displayVP2 vaccines (S/C, S/C-in oil and orally) were able to protect the chickens against the vvIBDV challenged virus with the best result via the oral route (93.34%). In addition to that, the phage-mediated VP2 vaccine given orally was able to protect the chickens (92.31%) against the ND genotype VII challenged virus. Phage-display VP2 and phage-mediated VP2 have no detrimental effects on the bursae. The F-based vaccines (pha.Dis.-F and pha.Med.-F) were not able to protect the chickens against the challenged virus. Though F-based vaccines were able to delay chicken mortalities following the challenge.